Citizen participation in managing water: Do Conversatorios generate collective action? - Córdoba, Diana M.; White, D. (CGIAR Challenge Program on Water and Food, 2011)
A central challenge for effective watershed management is improving the welfare of residents who live in upper catchments while providing adequate environmental goods and services to people and areas downstream. A CPWF project, Sustaining Collective Action Linking Economic and Ecological Scales in Upper Watersheds (SCALES), addressed this challenge in three sites. 1 This document is an evaluation of a project activity that intended to enhance collective action in one site: the Coello watershed of Colombia.